Mediators in the randomized trial of Child- and Family-Focused Cognitive-Behavioral Therapy for pediatric bipolar disorder. (October 2016) - MacPherson, Heather A.; Weinstein, Sally M.; Henry, David B.; West, Amy E.
Abstract: Mediation analyses can identify mechanisms of change in Cognitive-Behavioral Therapy (CBT). However, few studies have analyzed mediators of CBT for youth internalizing disorders; only one trial evaluated treatment mechanisms for youth with mixed mood diagnoses. This study evaluated mediators in the randomized trial of Child- and Family-Focused CBT (CFF-CBT) versus Treatment As Usual (TAU) for pediatric bipolar disorder (PBD), adjunctive to pharmacotherapy. Sixty-nine children ages 7–13 with PBD were randomly assigned to CFF-CBT or TAU. Primary outcomes (child mood, functioning) and candidate mediators (family functioning, parent/child coping) were assessed at baseline and 4-, 8-, 12- (post-treatment), and 39-weeks (follow-up). Compared with TAU, children receiving CFF-CBT exhibited greater improvement in mania, depression, and global functioning. Several parent and family factors significantly improved in response to CFF-CBT versus TAU, and were associated with the CFF-CBT treatment effect. Specifically, parenting skills and coping, family flexibility, and family positive reframing showed promise as mediators of child mood symptoms and global functioning. Main or mediating effects for youth coping were not significant. CFF-CBT may impact children's mood and functioning by improving parenting skills and coping, family flexibility, and family positive reframing. Findings highlight the importance of parent coping and family functioning in the treatment of PBD. Highlights: CFF-CBT improved children's manic and depressive symptoms and global functioning. CFF-CBT improved parent coping, family flexibility, and family positive reframing. Parent coping and family functioning showed promise as mediators of CFF-CBT. CFF-CBT may improve child outcomes via enhanced parent coping and family functioning.